Perbaikan Status Gizi Siswa TK Aisiyah Bustanul Athfal dengan Intervensi Makanan Cair Berbasis Tepung Beras Merah - Slamet Widodo; Rosa Rahayu; Andi Hudiah (Seminar Nasional LP2M UNM, 2019)
Abstract. The research objective is the participation of liquid food substitution of soybean husk flour to the nutritional status of children under five years. The design of the Randomized Controlled Trial (RCT) Single Blind Pre-post Study. The number of respondents 30, given liquid food for 30 days. Before and after the intervention measurements of body weight, body height. Paired t-test analysis method. Research controls for energy 165 and 2.6 Kcal, control 152 ± 3.96 Kcal, protein control 11.3 ± 2.1 g; treatment 13.2 ± 4 g. Changes in control body weight 18.3 ± 3.56 kg to 18.67 ± 3.56 kg, treatment 19.5 ± 2.35 cm to 19.8 ± 5.56 cm. Weight gain after consuming liquid food Improve the body of malnourished children to become normal children. Conclusion Nutritious feeding for 30 days improves nutritional status Keywords: Malnutrition, Liquid Food, Ari Soybean Flour